2019
DOI: 10.1136/bmjpo-2018-000371
|View full text |Cite
|
Sign up to set email alerts
|

Can social robots help children in healthcare contexts? A scoping review

Abstract: ObjectiveTo review research on social robots to help children in healthcare contexts in order to describe the current state of the literature and explore future directions for research and practice.DesignScoping review.Data sourcesEngineering Village, IEEE Xplore, Medline, PsycINFO and Scopus databases were searched up until 10 July 2017. Only publications written in English were considered. Identified publications were initially screened by title and abstract, and the full texts of remaining publications were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 65 publications
1
68
0
1
Order By: Relevance
“…Some reviews explore the use of robotics in therapy and health care context (e.g. Dawe et al., 2019 ; Istenic Starcic and Bagon, 2014 ). Differently, our review focuses on the evaluation of outcome of ER, as defined above.…”
Section: Discussionmentioning
confidence: 99%
“…Some reviews explore the use of robotics in therapy and health care context (e.g. Dawe et al., 2019 ; Istenic Starcic and Bagon, 2014 ). Differently, our review focuses on the evaluation of outcome of ER, as defined above.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance of robots in healthcare has been found to be mixed and can vary considerably depending on the function and appearance of the robot [34]. Despite the potential that social robots have to alleviate the ever-growing demands on healthcare professionals [34,35], low levels of acceptance can prove detrimental to the development and utilisation of such technology [34,36]. Therefore, a broader understanding of the extent to which social robots are accepted in healthcare and other settings; along with factors that are associated with acceptance is needed.…”
Section: Acceptance Of Social Robotsmentioning
confidence: 99%
“…In a recent medical scoping review, Dawe et al [6] surveyed the potential uses of social robotics in children's healthcare contexts and found potential benefits of using social robots to help children who require short-and long-term hospitalisation, as well as intensive care. This review also identified several important gaps in this research area, which we plan, in part, to address.…”
Section: Socially Assistive Robotics In Healthcarementioning
confidence: 99%